FSR 2011
DOI: 10.26536/fsr.2011.16.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Body Satisfaction: An Examination of Familial and Individual Level Variables

Abstract: ABSTRACT. This study investigated gender differences in body satisfaction in college students. Participants (195 males and 340 females) self-reported weight and height (in order to calculate BMI). In addition, attachment (to mother and father), dieting behaviors, perceived parental control, global self-worth, and body satisfaction were measured and examined in relation to satisfaction with one's body. Lower BMIs were associated with a higher degree of body satisfaction and higher self-worth scores among female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
2
4
1
Order By: Relevance
“…In the current study, the men were essentially equally aroused pre- and post-vignette. This finding could lend contradiction to the previously assumed norms in the literature that men do not care about body image [ 61 ]. However, men may still not care about their body image, but may be interested in the image of others, which in this vignette happened to be a female.…”
Section: Discussioncontrasting
confidence: 85%
“…In the current study, the men were essentially equally aroused pre- and post-vignette. This finding could lend contradiction to the previously assumed norms in the literature that men do not care about body image [ 61 ]. However, men may still not care about their body image, but may be interested in the image of others, which in this vignette happened to be a female.…”
Section: Discussioncontrasting
confidence: 85%
“…Given that the magnitudes of the associations were small in all regression analyses, it emphasized on this issue that BID is somewhat complex rather than unidirectional as presented in the current framework. It is a cross-cultural phenomenon, and also many other factors such as social (age, sex and educational level), familial (parental control), religious, acculturation level and media exposure, parenting style, birth weight and breast feeding are responsible for changes in BMI or the relationship between BID and body weight status which should be considered for future studies on body satisfaction [19,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers support the idea that there are gender disparities in adolescent self-esteem with some claiming that girls having lower self-esteem [27] [29] and others found that boys have lower self-esteem [30] . These differences might be explained by the different ages and cultures investigated.…”
Section: Discussionmentioning
confidence: 99%